A Note on Effect of Storage of Date Palm (Phoenix dactylifera L.) Pollen Grains on Their Germination and Date’s Fruit Setting - Mohamed, Moawia E.; El-Hag, Khalid Hamza; Ibrahim, Maha Abdalla Albashir; Elnagib, Osman Ahmed; Adam, Amal Saad (University of Khartoum Journal of Agricultural Sciences, 2023)
This investigation was initiated to study the effect of different storage methods on in vitro germination of date palm pollen grains as well as on fruit-setting. The collected pollen grains were stored in a refrigerator, freezer and freezer after being immersed in liquid nitrogen. After one year of storage, pollen viability was evaluated in terms of in vitro germination percentage and fruit-setting. The results revealed that the highest germination percentage and fruit-setting were associated with fresh pollen grains stored in the freezer followed by storage in freezer after immersion in liquid nitrogen and storage in the refrigerator. These results indicated that well dried pollen grains could be stored in fairly viable state until the following season in a freezer or a refrigerator.